Long-lasting potentiation and epileptiform activity produced by GABAB receptor activation in the dentate gyrus of rat hippocampal slice - Burgard, EC (J Neurosci, 1991)
Bath application of the GABAB receptor agonist baclofen produced a concentration-dependent long-lasting potentiation (LLP) of the evoked population spike in the dentate gyrus of rat hippocampal slices. A high concentration of baclofen (5 microM) also produced a loss of inhibition that was manifested as the appearance of epileptiform, multiple evoked population spikes and a decrease in paired-pulse inhibition. Both baclofen-induced potentiation and epileptiform activity could be blocked or significantly reduced in slices from pertussis toxin-treated animals (1 microgram, intradentate) or in slices pretreated with the NMDA receptor antagonist D-(-)-2-amino-5-phosphonovaleric acid (10 microM). At a concentration that had no significant effect on individual evoked responses (0.1 microM) but still produced a loss in paired-pulse inhibition, baclofen facilitated the induction of beta- adrenergic receptor-mediated LLP. LLP was induced in the dentate gyrus by bath application of 1 microM, but not 0.1 microM, isoproterenol. Coapplication of baclofen and isoproterenol, both at a concentration (0.1 microM) that individually had no effect on the population spike, produced a synergistic LLP of the population spike. We propose that baclofen produces a selective disinhibitory effect in the granule cell layer of the dentate gyrus by inhibiting the activity of GABAergic interneurons. At a low concentration, the subtle loss of inhibition can facilitate the induction of isoproterenol-induced LLP. At a high concentration, baclofen can produce an LLP that is probably induced by a loss of inhibition.